Beyond Physical Withdrawal: A Thematic Analysis of the States and Challenges of the Socially Withdrawn in China as Depicted on SNS - Zhang, Xiaomeng; Chen, Shuo; Takai, Jiro (Intercultural Communication Studies, 2025)
Social Withdrawal (SW) refers to a phenomenon where people, especially the young generation, avoid social activities, and confine themselves to their homes. This issue has become a significant public concern in many countries, including China, since socially withdrawn individuals (SWers), despite their potential, may contribute little to society. A major challenge in studying SW lies in the reluctance of these individuals to participate in traditional surveys or interviews, making it difficult to approach their inner worlds and lived experiences. To address this limitation, this study employed an innovative approach by analyzing the social networking site (SNS) activities of SWers. Specifically, we conducted a thematic analysis of naturally occurring data from online blog communities dedicated to SW in China. This method enabled us to explore the lives, emotions, and thoughts of SW individuals in a non-intrusive manner. Our findings revealed two overarching themes defined as: (1) the states of SW individuals, and (2) the challenges they face in reintegrating into society. Building on these insights, we discuss the implications of our findings, propose theoretical frameworks and put forward a series of practical suggestions for their social reintegration.